Cambridge paperback guide to literature in English. - Ousby, Ian. (New York : Cambridge University Press, 1996)
A compact version of the authoritative and acclaimed Cambridge Guide to Literature in English. Over 4000 entries provide quick and easy reference to writers and works from the classics of English literature to the best of modern writing; literature in English from around the world; novelists, poets, playwrights, critics, journalists, essayists; literary concepts, rhetorical terms, movements, groups; and detective writing, science fiction, children's literature
Keywords: English literature. -- Dictionaries; Commonwealth literature (English). -- Bio-bibliography.; Commonwealth literature (English). -- Dictionaries